ANALISIS KARAKTERISTIK USAHA PERTANIAN KOTA DI KOTA PONTIANAK - B61108029, RIANDA HANIS (Jurnal Ekonomi Daerah (JEDA), 2015)
ABSTRACT Agriculture is a marginal economic activities thatÂ  can be found in the city and suburbs in Pontianak. Although classified as a sector of the economy that provide a small share in GDP Pontianak, agriculture is still the right activities performed by most people of Pontianak city. BPS data show that the structure of the economy in some big cities in Java such as Jakarta and Yogyakarta, the share of agriculture in its GDP does not exceed 0.5% during the period of seven years (2006-2012). The aims of this are (1) to identify offenders who farm in Pontianak, (2) to access the main motivations of farmers in agricultural activities and (3) to identify the status of the land used by farmers for agricultural activities. The sample in this study are 100 farmers spread across the city of Pontianak. Method used in this study is the descriptive qualitative using frequency distribution table. The conclusion of this study are that farmers of Pontianak city majority of men with an aged range mostly 35-54 years and most of the inhabitants are Javaness and Maduraness. The level of education of farmers is low and farmers are less able get other job except farming, so the economic factor is the main motivation of farmers in agricultural activities in Pontianak city. Hobby is dominant factor in motivating farmers involved in urban agriculture. Land used by farmers are idle land belonging to other people and the government, and some are on their own land in the form of yard and porch. Keywords: Urban Agriculture, Pontianak City.